(untitled) (Journal of Misan Researches, 2020)
This study has dealt with the criminal liability of cyber-blackmail through social media which is an extremely dangerous offence that affects the individual and society. The recent scientific evolution that has surfaced in recent decades contributed to the development of the humanitarian communication methods, which brought the distant, shortened time and effort and turned the world into a small village. These communication methods are characterized by the high quality and tremendous digital potentials which aided communication process at all levels and changed the humanitarian parameters movement from the state of primitive and stagnation to vitality and advancement. Social media is one of these modern methods that emerged to make a positive changes and a huge progress in the humanitarian communication all over the world. Despite the numerous advantages and of the social media and the revolution that has brought about the movement of societies, a segment of society has not refrained from using these technologies as a means of assaulting others, through various offences including cyber-blackmail. The openness, lack of restrictions and massive supervision over social media have helped to spread these crimes, leading cyber-blackmail offence to become a phenomenon that penetrates the Arab and Iraqi society in particular, threatens its foundations and goes for the jugular. Among the most important objectives of any civilized society is achieving security for its individuals and making them feel safe in their lives. Because of the gravity of this crime, the Iraqi criminal judiciary has tried to keep pace with developments on the criminal scene, despite the lack of legislation that criminalizes this type of newly introduced crimes, relying on general rules in the Iraqi Penal Code No. 111 of 1969 amended, by criminalizing cyber-blackmail, considering it an explicit threat, and holding the perpetrator a criminal liability and then imposing a penalty against him.